Use of tranexamic acid in dogs with primary immune thrombocytopenia: A feasibility study - Olivares, Gerard; Sharman, Mellora; Miller, Rachel; Kisielewicz, Caroline; Seth, Mayank (Frontiers in Veterinary Science, 2023)
Objective The aim of this feasibility study is to evaluate the use of tranexamic acid and its safe use alongside standard therapy in dogs with primary immune thrombocytopenia (ITP). Design This is a cohort feasibility study involving 10 dogs diagnosed with primary ITP that received standard therapy for ITP including corticosteroids, a single dose of vincristine, and omeprazole. Dogs were randomly divided into either the control group (n = 6) or the group receiving tranexamic acid (TXA group, n = 4). Key findings The mean time from the start of treatment until remission was 5 days in the TXA group and 6 days in the control group (P = 0.69). Two dogs, one in each group, did not achieve remission. Clinical bleeding scores were not significantly different between both groups (p = 0.43), and the median blood volume administered was 37.5 ml/kg for the TXA group and 9.72 ml/kg for the control group (p = 0.084). Three out of the four dogs receiving TXA of 20 mg/kg IV started vomiting within 15 min of administration and were given a reduced dose of 15 or 10 mg/kg IV. Conclusion Tranexamic acid did not confer a clinical benefit in this small cohort study and was associated with a high incidence of vomiting. This study provides useful information for the design of future trials in dogs with ITP receiving tranexamic acid including outcome measures and safety.